Revised upper limb module for spinal muscular atrophy: 12 month changes. Issue 4 (7th February 2019) - Pera, Maria Carmela; Coratti, Giorgia; Mazzone, Elena S.; Montes, Jacqueline; Scoto, Mariacristina; De Sanctis, Roberto; Main, Marion; Mayhew, Anna; Muni Lofra, Robert; Dunaway Young, Sally; Glanzman, Allan M.; Duong, Tina; et al.
Abstract: Introduction : The aim of the study was to assess 12 month changes in upper limb function in patients affected by spinal muscular atrophy type 2 and 3. Methods : Longitudinal 12 month data was collected in 114 patients, 60 type 2 and 54 type 3, using the Revised Upper Limb Module. Results : The 12 month changes ranged between ‐7 and 9 (mean: ‐0.41; SD: 2.93). The mean changes were not significantly different between the three spinal muscular atrophy groups (‐0.45 in type 2, ‐0.23 in non‐ambulant type 3 and ‐0.34 in ambulant type 3, p = 0.96) and the relationship between 12 month change and age classes was not significantly different among the three types of SMA patients. Discussion : Our results confirm that the Module explores a wide range of functional abilities and can be used in ambulant and non‐ambulant patients of different ages in conjunction with other functional scales. Muscle Nerve 59:426–430, 2019